Gastrointestinal stromal tumour in pregnancy - Stubbs, Benjamin Michael (BMJ Publishing Group, 2011)
Gastrointestinal stromal tumour (GIST) in pregnancy is rare. There have been only three previously reported cases, all of which have been diagnosed on postoperative histology. The authors present the first case of a preoperatively diagnosed GIST arising in a 31-year-old pregnant woman. With a suspected diagnosis, the patient was managed through a combined obstetric and upper gastrointestinal multidisciplinary team meeting, resulting in planned early caesarean section and surgical removal of the tumour. This case emphasises the fact that early and effective multidisciplinary discussion allows for proper treatment planning and more informed patient decisions.